2019
DOI: 10.1002/ijc.32323
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and EZH2 cooperate in regulation of prostate cancer stem cell phenotype

Abstract: Prostate cancer (PCa) is the second most common malignancy and the sixth leading cause of cancer-related death among men worldwide. Prostate carcinogenesis is driven by the accumulation of genetic and epigenetic aberrations, which regulate cancer cell transition between a stem-and nonstem-cell state and accelerate tumor evolution. Elevated expression of enhancer of zeste homolog 2 (EZH2) histone methyltransferase, a core member of the polycomb repressive complex 2 (PRC2), results in cancer progression through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 52 publications
(95 reference statements)
4
53
0
Order By: Relevance
“…EZH2 is aberrantly expressed in glioma and has strong effects on PCa proliferation and metastasis [28][29][30]. Studies show that EZH2 functions in the maintenance of cancer stem-like cell (CSC) properties [31]. CSCs take part in tumor proliferation, recurrence, invasion, and chemoradioresistance, which makes a new concept of tumorigenicity and progression [32].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is aberrantly expressed in glioma and has strong effects on PCa proliferation and metastasis [28][29][30]. Studies show that EZH2 functions in the maintenance of cancer stem-like cell (CSC) properties [31]. CSCs take part in tumor proliferation, recurrence, invasion, and chemoradioresistance, which makes a new concept of tumorigenicity and progression [32].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 not only promotes the formation of cancer stem cells, but also expand the aggressive cancer cells population and lead to cancer progression [57]. Furthermore, EZH2 can also co-regulate prostate cancer stem cell properties with BRCA1 [58].…”
Section: Discussionmentioning
confidence: 99%
“…In the genes of MEmagenta module ( Supplementary Table S1), we found that the known genes closely related to cancer stemness in non-prostate cancer, such as BRCA1 [31], EZH2 [31], FOXM1 [32], CDC20 [33] and CDCA8 [34], were all clustered in this module, indicating these genes were also closely related to the stemness of prostate cancer cells. From supplementary table S1, we also found that EZH2 was the most signi cant gene in the correlation with stemness of PCa cells.…”
Section: Correlation Analysis Between Cancer Cell Stemness and Clinicmentioning
confidence: 92%
“…Yi and colleagues observed abnormal DNA methylation of CD133, a CSC marker, in colorectal and glioblastoma tumors [ 236 ]. Gorodetska and colleagues observed that EZH2/BRCA1 signaling mechanisms play an important role in the maintenance of prostate CSCs properties [ 238 ]. EMT aid in the generation of cells with stem cell characteristics and is modulated by epigenetic mechanisms [ 239 , 240 ].…”
Section: Properties Of Cancer Stem Cellsmentioning
confidence: 99%